To the question about the layout of the racks in the warehouse - Ilesaliev D.I. (Научно-технический вестник Брянского государственного университета)
Warehouses, which are located at points of transshipment of cargo from one type of transport on the other, play a sig-nificant role in the transformation of cargo to further the most effective transportation of goods. The location of racks and longitudinal passages are important in the work of transhipment warehouse. Typically, racks and longitudinal pas-sages are perpendicular to each other, the article proposes a radical change with the "euclidean advantage". This is an-other way of designing warehouses for efficiency overload packaged cargo in the supply chain. Purpose is to reduce the mileage for one cycle of the loader from loading and unloading areas to storage areas.